Design of glass containers for submarine carbon storage. Issue 3 (16th December 2021) - Fu, Cheng; Cefis, Nicola; Cremonesi, Massimiliano; Perego, Umberto; Caserini, Stefano; Grosso, Mario
Abstract : This work deals with the preliminary design of glass containers to be deposited on the seabed at 2000 m depth after being filled with liquefied carbon dioxide (CO2 ) at a pressure of 10 MPa. The specific purpose is to provide preliminary structural analyses of the containers to be employed in a novel patent CO2 storage method called confined submarine carbon storage (CSCS). The core steps of the CSCS technology are the container manufacturing and filling with high‐pressure liquid CO2 . Consequently, the container geometry, material properties and structural response are the most critical aspects in the container design. Due to the low cost and to the high stability in salty environment, glass has been identified as a suitable material for the CSCS technology. Furthermore, the high compressive resistance allows glass containers to be deposited on the seabed where the external water pressure exceeds the internal pressure of liquefied carbon dioxide. On the other hand, the limited tensile resistance of glass requires a careful shape design. The glass containers have to be designed to withstand stresses generated during their entire working life. This includes CO2 filling, the launching, the impact with the seabed and the final piling up and stacking of a huge number of containers. Finite element analyses have been performed in order to define the container shape, conjugating an acceptable storage capacity with a safe mechanical response during both the filling and deposition phases. Abstract : The work deals with the preliminary design of glass container to meet the structural aspects of the confined submarine carbon storage (CSCS) technology. Borosilicate glass has been chosen to be the container material for its high compressive strength and chemical resistance in salty environment. Finite element analyses have been performed in order to define the container shape, conjugating an acceptable storage capacity with a safe mechanical response during the container entire working life.